2001
DOI: 10.1097/00004347-200107000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Endometriosis and Clear Cell Carcinoma, Leiomyomatosis Peritonealis Disseminata, and Endometrial Adenocarcinoma: An Unusual, Pathogenetically Related Association

Abstract: A 42 year-old female with a preoperative clinical diagnosis of ovarian cancer underwent laparotomy which revealed leiomyomatosis peritonealis disseminata (LPD) in the peritoneum and omentum and a left ovarian endometriotic cyst associated with a clear cell carcinoma. A grade 1, superfically invasive villoglandular endometrial endometrioid adenocarcinoma was also found. Microscopically, the endometriotic cyst wall contained an extensive peripheral band-like condensation of stromal cells. These cells were strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…Our case of myoid UTROSCT found in ovarian endometriosis was indeed complex, since it was also associated with leiomyomatosis peritonealis disseminata (LPD). The association of LPD and endometriosis has often been reported and could reflect the coexistence of different metaplastic phenotypes in response to hormonal stimulation 10 . This is the first case of extrauterine myoid UTROSCT associated with bilateral ovarian surface endometriosis.…”
Section: Antibodiesmentioning
confidence: 72%
See 1 more Smart Citation
“…Our case of myoid UTROSCT found in ovarian endometriosis was indeed complex, since it was also associated with leiomyomatosis peritonealis disseminata (LPD). The association of LPD and endometriosis has often been reported and could reflect the coexistence of different metaplastic phenotypes in response to hormonal stimulation 10 . This is the first case of extrauterine myoid UTROSCT associated with bilateral ovarian surface endometriosis.…”
Section: Antibodiesmentioning
confidence: 72%
“…The association of LPD and endometriosis has often been reported and could reflect the coexistence of different metaplastic phenotypes in response to hormonal stimulation. 10 This is the first case of extrauterine myoid UTROSCT associated with bilateral ovarian surface endometriosis. In the present case, the ovarian myoid UTROSCT represented a small but prominent neoplastic change that did not involve the ovarian parenchyma and, not unsurprisingly, was initially diagnosed as a granulosa cell tumour.…”
mentioning
confidence: 80%
“…This would parallel a mechanism analogous to that giving rise to monoclonal peritoneal proliferations of such diverse tissues as smooth muscle (Guarch et al, 2001;Nogales et al, 1978) and epithelia such as endometrial (Clement et al, 2007), tubal-(Dallenbach-Hellweg et al, 1995Donne et al, 1998) andendocervical (Liu et al, 2009), which would originate in stem cells with a capacity to develop into Müllerian cell lines under the influence of hormonal growth factors. This has been aptly called the secondary Müllerian system (Lauchlan et al, 1994), which is not restricted to the peritoneum, but also present in the urinary bladder (Donne et al, 1998), ureter (Nogales et al, 1999), pleura and even in the abdominal and axillary lymph nodes (Stolnicu et al, 2011).…”
Section: Multifocal Peritoneal Metaplasia Induced By Growth Factorsmentioning
confidence: 99%
“…Moreover, atypical endometriosis has been described as a precursor lesion that can lead to certain types of ovarian cancer [11,12,13,14,15]. Other authors have also suggested a hormonal dependence or a relationship with other hormone-dependent pathologies in this type of association [16,17]. Endometriosis-induced inflammation and the auto- and paracrine production of sex steroid hormones could contribute to ovarian tumor genesis because these changes provide a microenvironment that favors the accumulation of sufficient genetic alterations and endometriosis-associated malignant transformation [15].…”
Section: Introductionmentioning
confidence: 99%